Pengaruh Suplementasi Vitamin C, Vitamin E, dan Kombinasinya Terhadap Penurunan Kadar Low Density Lipoprotein Serum pada Pasien Penyakit Ginjal Kronis Stadium V yang Dilakukan Hemodialisis - Dewi, Ayu Kusuma; Purwanto, Bambang; Wiboworini, Budiyanti (Jurnal Kedokteran Indonesia, 2012)
Background:Low density lipoprotein (LDL) cholesterol is a prognostic factor for hemodialysis mortality through atherosclerosis mechanism. Vitamin C and E have been well known as anti-oxidants that reduced LDL cholesterol. However, there were no studies have been done to address the effectiveness of vitamin C, E, and its combination on lowering LDL in patients with hemodialysis. This study aimed to determine the effect of vitamin C, E, and C and E combination on LDL cholesterol. Methods:A randomized controlled trial was conducted in 64 patients receiving hemodialysis at RSUD Dr.Moewardi(RSDM) Surakarta. The sample was taken at random and then divided into 4 groups: placebo, vitamin C (500 mg), vitamin E (400 mg), and vitamin C + E combination. The treatment lasted for 30 days. LDL cholesterol before and after treatment were analyzed at the Clinical Pathology division, RSDM. The reduction in LDL cholesterol before and after treatment was analyzed using One Way Anovaand (pair-wise) Post-Hoc Test. Results:One Way Anovashowed statistically significant reduction in LDL cholesterol between groups (p<0.001). Post hoc testshowed that vitamin C, vitamin E, or its combination reduced LDL cholesterol more than the placebo (p<0.001). Vitamin C and E administered in combination led to statistically significant lower LDL cholesterol than administered alone (p=0.002). There was no statistically difference in LDL cholesterol level between those provided with vitamin C and vitamin E. Conclusion: Vitamin C and E, individually or in combination, reduces LDL cholesterol. The highest reduction was achieved by vitamin C and E combination.Keywords: vitamin C, vitamin E, LDL cholesterol